Penguatan Proses Belajar Mengajar Melalui Penggunaan Teknik Place Mat - Ida Muliawati; Nelyza, Fita; Lismalinda, Lismalinda; Fahradina, Nova; Idami, Zahratul (Nawadeepa: Jurnal Pengabdian Masyarakat, 2022)
Teaching and learning process is inseparable from method and technique applied by educators, especially teachers as an attempt to improve the quality of output learning. Place mat technique is one of the cooperative learning methods in which students could work by themselves first and then team up with other group’s members in solving an issue or topic given. They can write down their idea as well as group’s opinion in a big place mat paper. Through the initial observation by interviewing some teachers of SMAN 1 Kuta Baro, Aceh Besar (Great aceh), it was found out that most of them never use this kind of technique in the classroom setting; they use some other kinds of techniques such as role play, jigsaw, numbered head together, and conventional technique. Therefore, the writers intend to carry on a community service to the students in the school as an effort to vary and increase the quality of teaching and learning process. This community service is hold on October 5-7, 2022 in SMAN 1 Kuta Baro, Great Aceh. This service is meant to train those teachers to be able to apply the technique during the teaching. Then, it is suggested to further community service activists to do the same activity in the rural areas as they basically need more input and insight from other educators in upgrading the way they teach.